PENGARUH SERVANT LEADERSHIP STYLE TERHADAP LOYALITAS KARYAWAN MELALUI PERAN MEDIASI KEPUASAN KARYAWAN (Study Pada Karyawan PT. Bank Syariah Mandiri Malang) - Ritaudin, Ahmad (Journal of Innovation in Business and Economics, 2016)
The purpose of this study was to how servant leadership style, employee performance and employee loyalty. To determine the effect of servant leadership style on employee loyalty, servant leadership style on employee satisfaction, employee satisfaction to employee loyalty, as well as the mediating role of employee satisfaction in PT. Bank Syariah Mandiri Malang. The samples in this research using random sampling with quota sampling technique gained 60 respondents employees at PT. Bank Syariah Mandiri Malang. Model structure equation modeling (SEM) type PLS (partial least Square), come to the conclusion: servant leadership style significant positive effect on employee loyalty; servant leadership style positive effect on employee satisfaction; Employee satisfaction is not significant positive effect on employee loyalty; and employee satisfaction does not mediate between servant leadership style on employee loyalty.Keywords: Employee Loyalty, Employee satisfaction, Servant Leadership Style, The Role of Mediation